The ATPase motor of the Chd1 chromatin remodeler stimulates DNA unwrapping from the nucleosome - Tokuda, Joshua M (Nucleic Acids Res, 2018)
Chromatin remodelers are ATP-dependent motors that reorganize DNA packaging by disrupting canonical histone–DNA contacts within the nucleosome. Here, we show that the Chd1 chromatin remodeler stimulates DNA unwrapping from the edge of the nucleosome in a nucleotide-dependent and DNA sequence-sensitive fashion. Nucleosome binding, monitored by stopped flow, was complex and sensitive to nucleotide, with AMP–PNP promoting faster binding than ADP·BeF(3)(–). Nucleosome unwrapping by Chd1, examined by bulk FRET, occurred in the presence and absence of nucleotide and did not require the Chd1 DNA-binding domain. In AMP–PNP conditions, Chd1 unwrapped one side of the Widom 601 DNA more easily than the other, consistent with previous observations of 601 asymmetry and indicating that Chd1 amplifies intrinsic sequence properties of nucleosomal DNA. Using small angle X-ray scattering (SAXS) with contrast variation, we found distinct DNA conformations depending on the nucleotide analog bound to Chd1: with AMP–PNP, DNA primarily unwrapped in-plane with the nucleosomal disk, whereas with ADP·BeF(3)(–), a significant fraction showed distinctive out-of-plane unwrapping as well. Taken together, our findings show tight coupling between entry/exit DNA of the nucleosome and the Chd1 ATPase motor, suggesting that dynamic nucleosome unwrapping is coupled to nucleosome binding and remodeling by Chd1.